2010
DOI: 10.1002/sia.3613
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of molecular surfaces with time‐of‐flight secondary ion mass spectrometry

Abstract: TOF-SIMS is a promising technique for evaluating biodevices due to its ultrahigh surface sensitivity. Since a cluster ion source such as C 60 + provides low collision energy per atom, time-of-flight secondary ion mass spectrometry (TOF-SIMS) with the cluster ion is useful for detecting the uppermost surface of molecules immobilized on a substrate, and therefore, enables the evaluation of the orientation of these immobilized biomolecules. Effects of TOF-SIMS with C 60 + were investigated in this study. A relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Therefore, it is indicated that the argon GC‐SIMS detects differences between the surface residues of the immobilized‐polypeptide molecules. Moreover, there was no difference in the peak at m/z 136 between the two enkephalins detected using conventional primary ion sources, such as Ga + and C 60 + 15…”
Section: Resultsmentioning
confidence: 91%
“…Therefore, it is indicated that the argon GC‐SIMS detects differences between the surface residues of the immobilized‐polypeptide molecules. Moreover, there was no difference in the peak at m/z 136 between the two enkephalins detected using conventional primary ion sources, such as Ga + and C 60 + 15…”
Section: Resultsmentioning
confidence: 91%